A shared value network model based on synergy theory in intelligent manufacturing - Pingping Gu; Jiahui Yu; Xianzhong Zhou; Hengrong Ju (Heliyon)
With the in-depth development and integration of science and technology, intelligent manufacturing has gradually become a trend in the manufacturing industry. However, it is difficult for the traditional business model to maximize the use of resources. To address these problems, a shared value network model based on synergy theory is first proposed, which consists of three layers: resource network layer, value connection layer and resource coordination layer. Then, to meet the market demand and maximize the value gain, the optimization scheme is given according to the coordination theory and priority strategy in the design of the operation mechanism of the shared value network model. Finally, the effectiveness of the proposed model is verified by analyzing an example in the actual industry.